THE MANAGEMENT OF MANGROVES IN AN URBAN SITUATION - Hutchings, P. A.; Recher, H. F. (Marine Research in Indonesia, 1977)
Sydney is an affluent city of nearly three million people surrounding three well developed estuaries and a shallow protected bay. These areas all originally had extensive wetlands of salt marsh, mangroves and sea-grass flats. The areas are now being rapidly reclaimed or destroyed by port development, marinas, canal estate development, playing fields, garbage tips or damaged by industry. They are also economically important fishing and oyster farming areas and the water masses are heavily used for recreation. In this paper we have selected three areas of wetlands in this region, threatened by different types of development and we discuss their ecology and their traditional biological attributes and the unique attributes that such areas have in an urban affluent society. These are their educational and recreational values to the community. We describe the planning of an education field centre adjacent to an urbanized wetland area and construction of boardwalks through the mangroves.